2021
DOI: 10.3389/fbioe.2021.770121
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate-Functionalized poly(ε-Caprolactone) Small-Diameter Vascular Grafts Enhance Vascular Regeneration via Sustained Release of Nitric Oxide

Abstract: Artificial small-diameter vascular grafts (SDVG) fabricated from synthetic biodegradable polymers, such as poly(ε-caprolactone) (PCL), exhibit beneficial mechanical properties but are often faced with issues impacting their long-term graft success. Nitric oxide (NO) is an important physiological gasotransmitter with multiple roles in orchestrating vascular tissue function and regeneration. We fabricated a functional vascular graft by electrospinning of nitrate-functionalized poly(ε-caprolactone) that could rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…If both random- and oriented-fiber membranes could maintain sufficient mechanical support in the early stage when implanted in vivo , there would be sufficient time to ensure new tissue regeneration. According to the literature ( De Valence et al, 2012 ; Zhou et al, 2014 ; Wang et al, 2017 ; Sevostyanova et al, 2018 ; Yin et al, 2020b ; Wen et al, 2020 ; Yang et al, 2021 ), when a graft was implanted in vivo , the endothelial cells gradually formed an intima, and smooth muscle cells and fibroblasts were also arranged along the axial direction of the graft, thus forming new blood vessel tissue. After 3 months, the vascular development was almost complete.…”
Section: Resultsmentioning
confidence: 99%
“…If both random- and oriented-fiber membranes could maintain sufficient mechanical support in the early stage when implanted in vivo , there would be sufficient time to ensure new tissue regeneration. According to the literature ( De Valence et al, 2012 ; Zhou et al, 2014 ; Wang et al, 2017 ; Sevostyanova et al, 2018 ; Yin et al, 2020b ; Wen et al, 2020 ; Yang et al, 2021 ), when a graft was implanted in vivo , the endothelial cells gradually formed an intima, and smooth muscle cells and fibroblasts were also arranged along the axial direction of the graft, thus forming new blood vessel tissue. After 3 months, the vascular development was almost complete.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously reported that quick endothelialization plays an essential role in vascular graft survival, as the endothelial cell layer can inhibit thrombosis and inflammation. 49,50,55 At 12 weeks post-implantation, more endothelial cells grew on the AICAR-modified grafts. Interestingly, there was more matrix deposition but without obvious thrombus-like tissues in the AICAR group.…”
Section: Discussionmentioning
confidence: 99%
“…In all, AICAR exhibited a promising pharmacological therapy to ensure better regenerative potential in vitro.Importantly, in vivo implantation also showed better remodeling processes in the AICAR-modified vascular grafts. It is previously reported that quick endothelialization plays an essential role in vascular graft survival, as the endothelial cell layer can inhibit thrombosis and inflammation 50,51,56. At 12-week Biomaterials Science Accepted Manuscript Open Access Article.…”
mentioning
confidence: 99%
“…NO also accelerates endothelium proliferation, as demonstrated in a study with arterial grafts. Although no significant difference was observed after 3 months, NO-releasing arterial grafts exhibited greater endothelium coverage than the non-NO-releasing graft after the first month [ 66 ]. For further information about NO’s role in cell proliferation, the interested reader is referred to reference [ 67 ].…”
Section: Nitric Oxide and Its Donorsmentioning
confidence: 99%